Do Mediterranean-type ecosystems have a common history?-insights from the Buckthorn family (Rhamnaceae) (2015)
Mediterranean?type ecosystems (MTEs) are remarkable in their species richness and endemism, but the processes that have led to this diversity remain enigmatic. Here, we hypothesize that continent?dependent speciation and extinction rates have led to disparity in diversity between the five MTEs of the world: the Cape, California, Mediterranean Basin, Chile, and Western Australia. To test this hypothesis, we built a phylogenetic tree for 280 Rhamnaceae species, estimated divergence times using eight fossil calibrations, and used Bayesian methods and simulations to test for differences in diversification rates. Rhamnaceae lineages in MTEs generally show higher diversification rates than elsewhere, but speciation and extinction dynamics show a pattern of continent?dependence. We detected high speciation and extinction rates in California and significantly lower extinction rates in the Cape and Western Australia. The independent colonization of four of five MTEs may have occurred conterminously in the Oligocene/Early Miocene, but colonization of the Mediterranean Basin happened later, in the Late Miocene. This suggests that the in situ radiations of these clades were initiated before the onset of winter rainfall in these regions. These results indicate independent evolutionary histories of Rhamnaceae in MTEs, possibly related to the intensity of climate oscillations and the geological history of the regions.